INTEGRATED FARMING SYSTEM (IES) FOR SUSTAINABLE AGRICULTURE: A CASE STUDY IN KARAIKAL, UNION TERRITORYOF PUDUCHERRY - I. Praveen Kumar; P.T. Suraj; S. Harikumar; Joseph Mathew (Indian Journal of Veterinary and Animal Sciences Research, 2025)
In India, small and marginal farmers, comprising 85% of the farming community, are pivotal to the rural economy. Addressing the rising demands amidst agricultural resource scarcity requires a holistic approach like Integrated Farming System (IFS). This method combines crop production, livestock, fishery, waste management, and poultry production synergistically. IFS boosts productivity, utilizes resources efficiently, and enhances food production, stabilizing income and ensuring nutritional security. A study in Karaikal district, Union Territory of Puducherry, which was an agricultural land and the entire farm revealed a benefitcost ratio of 1.75, demonstrating IFS's potential in overcoming population growth and resource challenges.